What is the association between the presence of comorbidities and the appropriateness of care for low back pain? A population-based medical record review study - Shanthi Ramanathan; Peter Hibbert; Louise Wiles; Christopher G. Maher; William Runciman (BMC Musculoskeletal Disorders, 2018)
Abstract Background Although “non-specific” in 90% of cases, low back pain (LBP) is often treated as an independent entity, even though comorbidities are commonly associated with it. There is evidence that some LBP may be related to chronic conditions or be a symptom of poor health. The purpose of this study was to clarify the extent of comorbidities amongst a cohort of Australian adults with LBP and examine if having concurrent conditions has any association with appropriateness of care for LBP. Methods A population-based sample of patients with one or more of 22 common conditions was recruited by telephone; consents were obtained to review their medical records. Trained surveyors extracted information from their medical records to examine the care patients received for their LBP with respect to ten indicators of appropriate care, ratified by LBP experts. Using LBP as the index condition, lists of self-reported comorbidities and those that were documented in medical records were compared. Medical records were reviewed and analysed with respect to appropriateness of care to identify any significant differences in care received between patients with LBP only and those with LBP plus comorbidities. Results One hundred and sixty four LBP patients were included in the analysis. Over 60% of adults with LBP in Australia had one of 17 comorbidities documented, with females being more likely than males to have comorbid conditions (63% vs 37%, p = 0.012). The more comorbidities, the poorer their reported health status (63% vs 30%, p = 0.006). Patients with comorbidities were significantly less likely to receive appropriate LBP care on nine of the ten LBP indicators (p < 0.05). Conclusions This study established that the presence of comorbidities is associated with poorer care for LBP. Understanding why this is so is an important direction for future research. Further studies using a larger cohort are needed to explore the association between comorbidities and appropriateness of care for LBP, to better inform guidelines and practice in this area.